Faktor Ekonomi, Pendidikan, Pengetahuan dan Sikap Ibu sebagai Prediktor Kejadian Gizi Kurang pada Balita - Lailaturohmah Lailaturohmah (FORIKES, 2024)
Nutrition for toddlers, especially at the rapid development stage aged 1-5 years, has a crucial role in supporting children's growth and development. Malnutrition in children can result in potentially detrimental nutritional conditions. This study aimed to evaluate the relationship between maternal attitudes, socio-cultural factors, and the incidence of malnutrition among toddlers (12-59 months) in Kotagajah, Central Lampung. This research implemented a cross-sectional design, involving 100 toddlers selected using accidental sampling technique. Data was collected by researchers through filling out questionnaires. Next, the collected data was analyzed using the Chi-square test. The results of the analysis showed that 36% of toddlers experience malnutrition. Hypothesis testing analysis for the role of each factor obtained a p-value of 0.000. Furthermore, it was concluded that economic factors, attitudes, education and knowledge of mothers were related to the incidence of malnutrition in toddlers.Keywords: malnutrition; toddlers; attitude; social; culture ABSTRAK Gizi pada balita, khususnya pada tahap perkembangan pesat usia 1-5 tahun, memiliki peran krusial dalam mendukung pertumbuhan dan perkembangan anak. Kekurangan gizi pada anak dapat mengakibatkan kondisi gizi kurang yang berpotensi merugikan. Penelitian ini bertujuan untuk mengevaluasi hubungan antara sikap ibu, faktor sosial budaya, dan kejadian gizi kurang pada balita (12-59 bulan) di Kotagajah Lampung Tengah. Penelitian ini menerapkan desain cross-sectional, yang melibatkan 100 balita yang dipilih dengan teknik accidental sampling. Data dikumpulkan oleh peneliti melalui pengisian kuesioner. Selanjutnya data yang telah terkumpul dianalisis menggunakan uji Chi-square. Hasil analisis menunjukkan bahwa 36% balita mengalami gizi kurang. Analisis uji hipotesis untuk peran masing-masing faktor didapatkan nilai p = 0,000. Selanjutnya disimpulkan bahwa faktor ekonomi, sikap, pendidikan, dan pengetahuan ibu dengan kejadian gizi kurang pada balita.Kata kunci: gizi kurang; balita; sikap; sosial; budaya